Indium‐Gallium‐Zinc‐Oxide Based Photoelectric Neuromorphic Transistors for Modulable Photoexcited Corneal Nociceptor Emulation. (11th August 2021) - Ke, Shuo; He, Yongli; Zhu, Li; Jiang, Zihan; Mao, Huiwu; Zhu, Yixin; Wan, Changjin; Wan, Qing
Abstract: Photoexcited corneal nociceptor (PCN) can recognize the noxious light stimulus and generate/transmit pain signals to the central nervous system, enabling the early‐warning and/or risk avoidance for the individual. Futhermore, central pain‐modulation can enhance pain or relieve pain, which greatly assists human adaptation to environments. Emulation of PCN and central pain‐modulation by neuromorphic devices will greatly improve the intelligence and adaptation of humanoid robots and artificial eyes in the real world. Here, amorphous indium‐gallium‐zinc‐oxide (a‐IGZO) based photoelectric neuromorphic transistors are fabricated with chitosan/graphene oxide nanocomposite electrolyte membranes as the gate dielectrics as well as the mechanical supports. PCN characteristics, including threshold, no‐adaptation, relaxation, allodynia and hyperalgesia, can be mimicked by the device and are attributed to the persistent photoconductivity performance of the IGZO channel. More importantly, central pain‐modulation containing central sensitization and analgesic effect is also successfully emulated by optoelectronic synergistic modulation. The results provide an important step toward to endow humanoid robots with visual intelligence and propel the development of neuromorphic perceptual systems. Abstract : Corneal nociceptor, as an essential sensory receptor in human eye, can recognize noxious stimulus, enabling the early‐warning and/or risk avoidance for the individual. Amorphous indium‐gallium‐zinc‐oxide (IGZO) based photoelectric neuromorphic transistor could be regarded as a promising candidate for such emulation. The hardware realization of the corneal nociceptor will largely extend the intelligent adaptability and cognition of artificial robots.